Disiplin Aparatur Sipil Negara pada Kantor Kesyahbandaran dan Otoritas Pelabuhan Kelas 1 Ambon - Hairia Musaad; Saartje Sarah Alfons; Dezonda Rosiana Pattipawae (Faculty of Law Pattimura University, 2021)
Introduction: Ambon Class 1 Port Authority and Concession in improving the smooth running of public services and ensuring the effectiveness, efficiency and discipline of employees, looking at employee work discipline regarding working days are days that are determined to work formally, working hours are the time determined to work formally.Purposes of the Research: This writing aims to identify and analyze the discipline of the Airport State Civil Apparatus and the Ambon Class 1 Port Authority have an effect on good governance.Methods of the Research: The method used in this research is the type of normative juridical research method, the type of descriptive analytical research, the source of legal materials, namely primary legal materials, secondary legal materials and tertiary legal materials. Legal Material Analysis and Legal Material Analysis Methods.Results of the Research: The results show that Government Regulation No. 53/2010 concerning Civil Servant Discipline is a legal basis for regulating the actions and behavior of Civil Servants in order to comply with all applicable regulations, so that their main duties and functions can be carried out properly. Civil servants who are suspected of committing disciplinary violations are summoned to be investigated by the official who has the authority to punish or other officials appointed by him.